Keogram data derived from auroral images taken by the all-sky EMCCD imager with a 777nm filter at Tromso, Norway - Yoshizumi Miyoshi; Keisuke Hosokawa; Shin-ichiro Oyama; ISEE IUGONET Metadata Management Group (名古屋大学, 2017)
Keogram data derived from auroral images taken by the all-sky EMCCD imager with a 777nm filter at Tromso, Norway. dataset